If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2y = 16.60 Solving 6x + 2y = 16.60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 6x + 2y + -2y = 16.60 + -2y Combine like terms: 2y + -2y = 0 6x + 0 = 16.60 + -2y 6x = 16.60 + -2y Divide each side by '6'. x = 2.766666667 + -0.3333333333y Simplifying x = 2.766666667 + -0.3333333333y
| 4(5)-4x=4 | | -4k(k+6)-(9k-6)=-14k | | 3x+2.5x=60 | | P=2(1.08)t | | 4.9t^2+17.9t+5=0 | | 12.8*0.25= | | X-90=4x | | 5a=7+8a | | 4x-2(x-4)=-6+4x+10 | | (10x^2+30x)=(2x^2-30x-75) | | -2x+5(-2x-6)=18 | | 3-(6s-15)=4s+8 | | 20x^2+25x+75=0 | | 3x+3=x-18 | | -16=x-10 | | 24-6k=6(k-4) | | 0.4y+0.65x=60 | | 24-6k=6k(4-k) | | 6(1+4a)=-114 | | 3(9y+3)-9=2y+21 | | 39+0.75x=x | | (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d | | 5t+6-2r=7r-10 | | y+9x^3y=0 | | 4x+1=4x-2 |